IMPLEMENTASI KEBIJAKAN PERTANAHAN (STUDI KASUS PADA BAGIAN PENDAFTARAN TANAH di KECAMATAN TAMPAN KOTA PEKENBARU) - Chayani, Dwi Anggun; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The many land conflicts in District Tampan making Land Policy for more seriouslyimplemented. Problem of this research is how implementation of policy of Land (Case StudyIn The Land Registration In The District Of The City Tampan Pekanbaru) and factorsinfluencing implementation of the policy. As for becoming intention of this research is toknow implementation of policy of Land (Case Study In The Land Registration In The DistrictOf The City Tampan Pekanbaru) and factors influencing implementation of the policy. Resultof this research indicates that Implementasi implementation of policy of land (Case Study InThe Land Registration In The District Of The City Tampan Pekanbaru) has not, runoptimalfashion. Factors infuencing in implementation of policy this land still lack of socialization togroup of target and lack of knowledge in land registration.Keyword: Policy, Implementation of Policy.